Asymmetric mechanosensitivity in a eukaryotic ion channel - Clausen, M; Jarerattanachat, V; Carpenter, E; Sansom, M; Tucker, S (National Academy of Sciences, 2017)
Living organisms perceive and respond to a diverse range of mechanical stimuli. A variety of mechanosensitive ion channels have evolved to facilitate these responses, but the molecular mechanisms underlying their exquisite sensitivity to different forces within the membrane remains unclear. TREK-2 is a mammalian two-pore domain (K2P) K+ channel important for mechanosensation, and recent studies have shown how increased membrane tension favors a more expanded conformation of the channel within the membrane. These channels respond to a complex range of mechanical stimuli, however, and it is uncertain how differences in tension between the inner and outer leaflets of the membrane contribute to this process. To examine this, we have combined computational approaches with functional studies of oppositely oriented single channels within the same lipid bilayer. Our results reveal how the asymmetric structure of TREK-2 allows it to distinguish a broad profile of forces within the membrane, and illustrate the mechanisms that eukaryotic mechanosensitive ion channels may use to detect and fine-tune their responses to different mechanical stimuli.